Dermatomyositis with Eosinophils - Isabella I. Sanchez; Henry O. Herrera; Ashley Elsensohn; Bonnie A. Lee; Christina N. Kraus (MDPI AG, 2023)
Dermatomyositis is an idiopathic inflammatory myopathy that often presents with symmetric proximal skeletal muscle weakness and characteristic skin findings. Typical skin biopsy findings include vacuolar changes of the basal layer, increased dermal mucin, and a predominantly lymphocytic infiltrate. We report a case of dermatomyositis presenting as intensely pruritic papules and plaques, with initial histopathology being atypical of dermatomyositis due to the presence of eosinophils. The initial biopsy demonstrated a superficial dermatitis with eosinophils, initially thought to represent a drug eruption. A second biopsy of the same cutaneous manifestation was performed at a later time given high clinical suspicion for dermatomyositis and demonstrated a more classic vacuolar interface dermatitis with increased mucin and an absence of eosinophils. Notably, increased pruritus was specifically associated with the lesion that demonstrated tissue eosinophilia. The case illustrates the importance of considering tissue eosinophilia in the histologic presentation of dermatomyositis.